The Mechanisms Underlying the Biological Response to Wear Debris in Periprosthetic Inflammation - Couto, M (2020)
Joint replacement surgery is the gold-standard therapeutic approach to treat patients with end-stage hip and knee arthritis, providing pain relief and joint function recovery. Despite the improvements in implant design and surgical techniques, revisions after total joint replacement are expected to grow. The periprosthetic inflammation, featured by the sustained inflammatory response to the implant debris, elicits the activation of osteoclasts and consequent periprosthetic osteolysis (PPOL), ultimately leading to implant aseptic loosening, which is the most common cause of long-term implant failure. There are currently no effective strategies to control periprosthetic inflammation, and long-term implant survival remains a major challenge in orthopedics. A broad knowledge of the mechanisms underlying the biological response to implant debris would support the development of novel and effective pharmacological strategies to manage PPOL and promote implant lifespan. In this review, a detailed description of the cellular and the molecular mechanisms underlying the biological response to implant debris is provided, highlighting the most recent findings. Furthermore, we reviewed novel therapeutic strategies that are being investigated to prevent inflammatory periprosthetic osteolysis.